ANFIS based hybrid solar and wave generator for distribution generation to grid connection - Manohar B S; Banakara Basavaraja (Institute of Advanced Engineering and Science, 2019)
With a long coastal border of about 7500 Kms, India would need an efficient option of hybrid power generation in the coastal region. Abundant availability of wave power and sunlight due to its closeness to equator makes it clear base for power generation from wave generator and the solar power. This paper develops the implementation, which combines both the wave generator and the PV array for a hybrid power delivery controlled using Adaptive Neuro Fuzzy Inference Engine (ANFIS) controller. The super capacitor is used for higher efficiency compared to batteries. It absorbs power and delivers power fast, where it is more important in wave generation as the power and voltage is not stable. The power delivery improvement in this hybrid system while different controllers like the PI and the ANFIS controller is analysed. There is a higher power delivery improvement when ANFIS controller is chosen.